Existence of Parallel Universes as Sacred Timelines: Narrative Concept in Modern Fictional Works - Saptanto, Deswandito Dwi; Dewi, Maya Kurnia; Nurjanah, Ratih Laily; Putri, Salma Rafita; Safinah, Irsya (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2023)
Multidimensional or often referred to as the vast and countless universe (multiverse) is currently a hot issue in modern society and many people believe that the existence of this diverse universe is real. The representation of the existence of this diverse universe has been shown in the television series which is an adaptation of the comic series titled ‘Loki’, then a collection of fairy tales traveling to a fantasy world titled ‘The Chronicles of Narnia’ which in the big screen version consists of three main series namely The Lion, The Witch, And The Wardrobe, Prince Caspian and The Voyage of The Dawn Treader, then a novel titled ‘Dark Matter’ and a film entitled ‘Everything Everywhere All at Once'. These works of fiction are similar to the concept of emphasizing the process of transformation from the real world as it is today and then moving to other universes in the story. The main character in the story experiences a multi-dimensional journey that is difficult to explain logically. This study uses qualitative descriptive methods using a comparative literary approach combined with semiotic theory and the concept of equilibrium in narrative theory to dissect and analyze the hidden meanings that appear in these works of fiction. The results obtained from this study are that the idea of multi-dimensional life, multi-universes and parallel universes has become a very popular thing in various works of modern fiction. The superiority of storytelling techniques like this gives the author freedom and flexibility in creating a work, and the idea of storytelling like this will trigger tremendous curiosity for the reader or audience.